Determining the minimum inhibitory concentrations of pyrazinamide against Mycobacterium tuberculosis clinical isolates at a neutral pH of 6.8 using the broth microdilution method - Tamblin, Maria; Shi, Wanliang; Chen, Liang; Reynolds, Jessica (Frontiers in Microbiology, 2025)
IntroductionPyrazinamide (PZA) is a critical component of first-line tuberculosis (TB) treatment. Misdiagnosis of PZA resistance can lead to serious consequences, highlighting the need for accurate and reliable PZA susceptibility testing. While broth microdilution is a cost-effective and widely used method for determining the minimum inhibitory concentrations (MICs) of antibiotics, its current application for PZA has been limited by the requirement for acidic conditions in conventional Mycobacterium tuberculosis culture media.MethodsIn this study, we determined the MICs of PZA against the clinical isolates of pyrazinamidase-positive M. tuberculosis at a neutral pH of 6.8 using a defined culture medium and the standard protocol of the broth microdilution method.ResultsThe results showed that PZA MICs could be reliably determined in M. tuberculosis clinical isolates, with values ranging from ≤12.5 to 100 μg/mL.DiscussionThis approach overcomes the limitations of existing acidic pH-based PZA susceptibility tests and provides a reliable, accurate, cost-effective method for detecting improved PZA resistance. Implementing this method could significantly enhance TB treatment, resistance surveillance, and efforts to combat drug-resistant TB.